MENJADI IBU TERBAIK: KONTESTASI WEST & ORIENT MOTHER DALAM TERJEMAHAN LITTLE FIRES EVERYWHERE - Kusumaningrum, Ayu Fitri (Adabiyyāt: Jurnal Bahasa dan Sastra, 2023)
Orientalism is synonymous with the Western male view of Eastern men and women. The discourse of Orientalism is a masculine discourse that rarely portrays women, especially mothers, as subjects of analysis. The problem of this research lies in the Orientalist discourse in the Indonesian version of the novel "Little Fires Everywhere" by Celeste Ng, which is approached from the viewpoint of women, particularly mothers, resulting in a contest to become the best mother. The mothers in this novel are divided into two categories: the West mother, represented by Elena Richardson, and the Orient mother, represented by Mia Warren. This study aims to reveal the contestation between the West and Orient mothers. This research uses a qualitative method, and the theoretical framework used is Orientalism, as proposed by Edward W. Said. This research found latent Orientalism in the West mother's perspective towards the Orient mother, resulting in competition to become the best mother figure. This research also found that both mothers failed to become the best mothers for their children, whether from the West or the Orient.